The Effect of Soaking Red Chili Seeds (Capsicum annum L.) with Various Trichoderma Species in Suppressing Chili Seed-Borne Pathogens Caused by Colletotrichum - Rani Selpia Siregar; Dini Puspita Yanty; Jumaria Nasution (CIB Nusantara, 2025)
Red chili (Capsicum annuum L.) is a horticultural plant that belongs to the Solanaceae family. Chili cultivation often encounters problems, namely anthracnose disease caused by the fungus Colletotrichum. This study aims to determine the most effective Trichoderma species for suppressing red chili seed-borne Colletotrichum pathogens. This study was conducted from March to April 2025. This research method used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. P0 = Control (Without soaking with Trichoderma suspension) P1 = Red chili seeds soaked with Trichoderma harzianum suspension for 9 hours P2 = Red chili seeds soaked with Trichoderma viride suspension for 9 hours P3 = Red chili seeds soaked with Trichoderma asperellum suspension for 9 hours P4 = Red chili seeds soaked with fungicide for 5 minutes. The parameters observed were: Germination percentage (%), seedling height (cm), and number of leaves (stalks). Trichoderma treatment significantly affected germination percentage, red chili seedling height, and leaf number. In terms of treatment percentage, P1, P2, and P3 were significantly different in red chili seed germination percentage, but the three treatments were not significantly different from P0 and P4. Soaking local chili seeds with various Trichoderma suspensions was best found in the types of Trichoderma viride and Trichoderma asperellum because it can be seen from the value of the results of the percentage of germination power, the average height of seedlings, and the number of leaves, the values ​​​​of Trichoderma viride and Trichoderma asperellum were the highest.